Activation of human monocytes for nitroblue tetrazolium reduction and the suppression of lymphocyte response to mitogens. - Zembala, M (1980)
Human peripheral blood mononuclear cells freed from polymorphs reduce nitroblue tetrazolium (NBT). This reduction is due to monocytes, i.e. adherent, phagocytic, esterase-positive cells with Fc receptors. Monocytes allowed to phagocytose zymosan show increased NBT reduction which under optimal conditions is 12.2 +/- 2.4 x 10(-9) mol . hr-1 . 10(-6) monocytes. Monocytes which have phagocytosed zymosan depress the mitogen response of human lymphocytes to PHA. This effect of 'activated' monocytes is due to a soluble inhibitory mediator which appears in the supernatant after culture for 24 hr. Its appearance requires protein synthesis. It is suggested that NBT reduction of peripheral blood mononuclear cells can be used as a test for the state of monocyte activation in disease. The possibility that activated monocytes may depress blast transformation in vitro in disease states is discussed.